Biogeochemical fingerprints of life: earlier analogies with polar ecosystems suggest feasible instrumentation for probing the Galilean moons. Issue 3 (July 2015) - Chela-Flores, J.; Cicuttin, A.; Crespo, M.L.; Tuniz, C.
Abstract We base our search for the right instrumentation for detecting biosignatures on Europa on the analogy suggested by the recent work on polar ecosystems in the Canadian Arctic at Ellesmere Island. In that location sulphur patches (analogous to the Europan patches) are accumulating on glacial ice lying over saline springs rich in sulphate and sulphide. Their work reinforces earlier analogies in Antarctic ecosystems that are appropriate models for possible habitats that will be explored by the European Space Agency JUpiter ICy Moons Explorer (JUICE) mission to the Jovian System. Its Jupiter Ganymede Orbiter (JGO) will include orbits around Europa and Ganymede. The Galileo orbital mission discovered surficial patches of non-ice elements on Europa that were widespread and, in some cases possibly endogenous. This suggests the possibility that the observed chemical elements in the exoatmosphere may be from the subsurface ocean. Spatial resolution calculations of Cassidy and co-workers are available, suggesting that the atmospheric S content can be mapped by a neutral mass spectrometer, now included among the selected JUICE instruments. In some cases, large S-fractionations are due to microbial reduction and disproportionation (although sometimes providing a test for ecosystem fingerprints, even though with Sim – Bosak – Ono we maintain that microbial sulphate reduction large sulphur isotope fractionation does not require disproportionation. We address the question of the possible role of oxygen in the Europan ocean. Instrument issues are discussed for measuring stable S-isotope fractionations up to the known limits in natural populations of δ34 ≈ −70‰. We state the hypothesis of a Europa anaerobic oceanic population of sulphate reducers and disproportionators that would have the effect of fractionating the sulphate that reaches the low-albedo surficial regions. This hypothesis is compatible with the time-honoured expectation of Kaplan and co-workers (going back to the 1960s) that the distribution range of 32S/34S in analysed extra-terrestrial material appears to be narrower than the isotopic ratio of H, C or N and may be the most reliable for estimating biological effects. In addition, we discuss the necessary instruments that can test our biogenic hypothesis. First of all we hasten to clarify that the last-generation miniaturized mass spectrometer we discuss in the present paper are capable of reaching the required accuracy of ‰ for the all-important measurements with JGO of the thin atmospheres of the icy satellites. To implement the measurements, we single out miniature laser ablation time-of-flight mass spectrometers that are ideal for the forthcoming JUICE probing of the exoatmospheres, ionospheres and, indirectly, surficial low-albedo regions. Ganymede's surface, besides having ancient dark terrains covering about one-third of the total surface, has bright terrains of more recent origin, possibly due to some internal processes, not excluding biological ones. The geochemical test could identify bioindicators on Europa and exclude them on its large neighbour by probing relatively recent bright terrains on Ganymede's Polar Regions.